A systematic review of surgical and interventional radiology procedures for pediatric idiopathic intracranial hypertension - Friso, Sofia; Giacobbo, Vittoria; Toscano, Luca Mattia; Baldo, Beatrice; Guariento, Chiara; Lacarra, Fabrizio; Pin, Jacopo Norberto; Ancona, Claudio; Sartori, Stefano; Causin, Francesco; Toldo, Irene (Frontiers in Pediatrics, 2024)
Background: Idiopathic intracranial hypertension (IIH) is defined as elevated intracranial pressure and consequent symptoms (mainly headache and visual deterioration) occurring in the absence of secondary causes. Surgical and interventional radiology procedures should be considered for refractory IIH and mainly include cerebrospinal fluid (CSF) diversion techniques, optic nerve sheath fenestration (ONSF), and venous sinus stenting (VSS). Our study aims to review the current literature on the application of these techniques in clinical practice.Methods: A systematic literature review on the surgical and interventional radiology treatment of IIH was conducted, focusing on ONSF, VSS and CSF diversion techniques. According to PRISMA guidelines, all reports published in PubMed in the last 30 years were considered, and among 722 papers, 48 were included in the present study, resulting in a total study population of 454 children or adolescents (11 months-17 years old).Results: 193/454 patients underwent an invasive approach, divided into CSF diversion (115/193), ONSF (65/193), VSS (11/193), cranial subtemporal decompression (8/193) and internal cranial expansion (9/193). 16/193 patients (8%) required reintervention due to relapsing symptoms or surgical complications, particularly those who underwent CSF diversion. Furthermore, 9/115 required shunt revision due to shunt obstruction or malfunction. We extracted data on the outcome of each procedure: 71/193 patients experienced a positive outcome with symptoms resolution or improvement, while 27/193 demonstrated a negative outcome.Discussion and conclusions: Severe and refractory cases of IIH are eligible for invasive treatments. CSF diversion is the most frequently used technique, despite its high failure risk and need for reintervention. ONSF has shown good results in terms of outcome and safety, particularly in children with visual symptoms. VSS is the most recent approach, indicated in children with stenosis of the venous sinus. In our study population, VSS demonstrated good results in terms of symptom resolution and need for reintervention, but its use remains limited to a few centers.